Assessment of Potential Review in Organizations through HAV MATRIX - Nugrani, Suci; Adiati, Rosatyani Puspita (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The background of this research is the importance of Talent Management in Human Resource Management (HRM). The purpose of Talent Management is to aim at ensuring employees are placed in roles that align with their potential and capabilities (Cummings & Worley, 2015a; Mondy & Martocchio, 2016). Organizations must adopt a systematic approach to identifying employee potential as a basis for strategic decision-making, including promotions, training, and succession planning (Gibson & Mitchell, 2011; Jooss et al., 2021). Potential review serves as a relevant method for objectively assessing individual strengths and weaknesses (Ardhi & Darusmin, 2020; Munandar, 2008). This study aims to support the talent management strategy at PT Z by evaluating employee potential through the Human Asset Value (HAV) Matrix. Amid increasingly complex business dynamics, the strategic management of human resources, particularly in identifying and developing talent, has become increasingly critical. PT Z conducted individual assessments as an initial step to map employee competencies and capacities to support optimal career development planning. A mixed-method approach, comprising psychological testing and interviews, was applied to analyze the data descriptively and qualitatively, resulting in a comprehensive employee profile of an individual serving as an Assistant Analyst for Organizational Culture. The study's findings indicate that the employee possesses strong developmental potential, categorized as "promotable," with a medium performance level and optimal capacity based on the HAV Matrix assessment. These results suggest that the employee is recommended for inclusion in the company's talent pool, with strategic implications for succession planning and sustainable career development at PT Z.Latar belakang dari penelitian ini adalah pentingnya Pengelolaan Talenta dalam Manajemen Sumber Daya Manusia (MSDM). Pengelolaan Talenta bertujuan memastikan karyawan berada pada posisi yang sesuai dengan potensi dan kapabilitasnya (Cummings & Worley, 2015b; Mondy & Martocchio, 2016b). Perusahaan perlu memiliki pendekatan yang sistematis dalam mengidentifikasi potensi karyawan sebagai dasar pengambilan keputusan strategis, seperti promosi, pelatihan, atau suksesi jabatan (Gibson & Mitchell, 2011; Jooss et al., 2021). Potential review menjadi salah satu metode yang relevan dalam mengungkap kekuatan dan kelemahan individu secara objektif (Ardhi & Darusmin, 2020; Munandar, 2008). Penelitian ini bertujuan untuk mendukung strategi manajemen talenta di PT Z dengan mengevaluasi potensi karyawan melalui Human Asset Value (HAV) Matrix. Di tengah dinamika bisnis yang semakin kompleks, pengelolaan sumber daya manusia secara strategis, khususnya dalam identifikasi dan pengembangan talenta, menjadi semakin penting. PT Z melaksanakan asesmen individual sebagai langkah awal untuk memetakan kompetensi dan kapasitas karyawan guna mendukung perencanaan pengembangan karier yang optimal. Pendekatan metode gabungan yang terdiri atas tes psikologi dan wawancara diterapkan untuk menganalisis data secara deskriptif dan kualitatif, sehingga menghasilkan profil karyawan secara komprehensif, yaitu individu yang menjabat sebagai Assistant Analyst Budaya Organisasi Temuan penelitian menunjukkan bahwa subjek memiliki potensi pengembangan yang kuat, dikategorikan sebagai "promotable" dengan tingkat kinerja sedang dan kapasitas optimal berdasarkan hasil asesmen HAV Matrix. Hasil ini mengindikasikan bahwa subjek direkomendasikan untuk dimasukkan ke dalam talent pool perusahaan, dengan implikasi strategis terhadap perencanaan suksesi dan pengembangan karier yang berkelanjutan di PT Z.